Teaching pronunciation - Attitudes of Teachers and Learners - Hrubešová, Magdaléna (Univerzita Pardubice, 2023)
This diploma thesis is focused on the attitudes of teachers and learners towards pronunciation in English. In the theoretical part, the historical perspective on teaching pronunciation is introduced, and then followed by the contemporary perspective on teaching pronunciation, which is based on the relevant curricular documents. Furthermore, an overview of basic terminology relevant to pronunciation is introduced and discussed in relation to teaching pronunciation. Lastly, the period of the young learner is discussed. The practical part focuses on the description of case study which aims to find out what are the attitudes of teachers and learners towards teaching pronunciation.
Výuka výslovnosti - postoje učitelů a žáků
Keywords: pronunciation; early school age; attitude; teaching pronunciation; linguistic competence; elementary school; výslovnost; mladší školní věk; postoj; vyučování výslovnosti; lingvistická kompetence; základní škola